1976
DOI: 10.1159/000102502
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Slow Negative Potential Shift (CNV) in the Thalamus

Abstract: In order to know the functional relationship between CNV recorded at the vertex and activity of the thalamic nucleus, the CNV at the vertex and the intrathalamic slow potentials responding to an S1-S2-R paradigm were recorded during thalamotomy under local anesthesia. It might be concluded that the activity of the medial thalamus and medial parts of the subthalamic area not only generate slow potential shifts corresponding to S1-S2-R, but also play an important role in controlling the CNV at the vertex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Earlier studies with monopolar recording during thalamic stereotactic surgery in humans showed the same findings (Baba et al, 1976). Using monopolar montages, premovement potentials with similar characteristics were recorded from contacts located in the putamen (Rektor et al, 2001) and subcortical white matter (Tsubokawa et al, 1976). Since the monopolar premovement potentials may reflect far field activity arising from structures between the intracerebral and scalp contacts, we used a bipolar montage between two consecutive contacts of the DBS electrode (i.e., 0–1, 1–2, 2–3), which picked up electrical signal from a small area close to the pair of recording contacts…”
Section: Neurophysiological Findingsmentioning
confidence: 99%
“…Earlier studies with monopolar recording during thalamic stereotactic surgery in humans showed the same findings (Baba et al, 1976). Using monopolar montages, premovement potentials with similar characteristics were recorded from contacts located in the putamen (Rektor et al, 2001) and subcortical white matter (Tsubokawa et al, 1976). Since the monopolar premovement potentials may reflect far field activity arising from structures between the intracerebral and scalp contacts, we used a bipolar montage between two consecutive contacts of the DBS electrode (i.e., 0–1, 1–2, 2–3), which picked up electrical signal from a small area close to the pair of recording contacts…”
Section: Neurophysiological Findingsmentioning
confidence: 99%